نقشۂ جما ل ِمصطفیٰ ﷺقرآن کے تنا ظر میں (Al-Qamar, 2020)
Holy Prophet (PBUH) had so infinite beauty that cannot be completely described by finite words on earth. It is impossible to comprehend the interminable and immense beauty of the Holy Prophet (PBUH). The example of the beauty of the Prophet (PBUH) is like the endless sea in which one and a half waves bounce and show themselves and no one can descend into the depths of the sea which is spread far and wide. The Creator of the universe has acknowledged His beauty in the Holy Qur'an. Many attributes of the Prophet (PBUH) are mentioned in verses of the Quran that depicts the level of excellence with which Allah made his Prophet (PBUH). This article is an attempt to sketch the beauty of the Holy Prophet (PBUH) in the context of the Quran.
Keywords: Prophet; sketches; beauty; Quran